Electronic Comics in Elementary School Science Learning for Marine Conservation - Syarah, E. S.; Yetti, E.; Fridani, L.; Yufiarti, Y.; Hapidin, H.; Pupala, B. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2019)
Marine education is essential in helping children to develop the knowledge, skills, and attitudes needed to preserve the environment, particularly for future coastal ecosystems. Effective marine education requires teachers to use proper strategies that will help children to value and care for the marine world. The purpose of this study was to determine the effectiveness of electronic comics to introduce marine conservation in elementary school. This study employed a quasi-experimental design model with paired t-test statistical analysis. The participants in this study involved three classes of elementary schools in Banten Province, Indonesia. There were 113 children and were divided into two experimental classes using electronic comics (laptops, computers, tablets, and mobile phones) and one control class using printed books. The results of this study showed a significant result in marine conservation knowledge of elementary school students in the experimental classes. In the control class, there was only a slight increase in the knowledge of marine conservation. The data analysis results revealed that children aged 6-8 years are more interested in learning using electronic comics compared to printed books. The findings also showed that elementary school students (aged 6-8 years) could recognize and comprehend marine conservation in science learning through electronic comics. The introduction to marine conservation could then be done using the latest technology that attracts children’s learning interest.